A chance of life. (10th December 2008) - Nott, David
Abstract : The surgeon David Nott, a Christian who does regular voluntary work abroad, made headlines last week when he recounted how he used instructions sent by text message to do a forequarter amputation on a boy in the Democratic Republic of Congo. Here he tells the story in his own words